“Em breve nos cinemas”: assimilação e articulação do formato trailer pela experiência cinematográfica brasileira - Jaber, Fernanda Affonso de André (2017)
The object of study of this dissertation is the film trailer in the context of Brazilian cinematic experience. From a historical perspective, this research clarifies how the relationship between the Brazilian trailer and the U.S. benchmark developed over time, and what were the influences of the imported object, both on the trajectory of the domestic trailer in the market and on its mode of discourse. The main concern was to understand where the trailers fit in the history of Brazilian cinema, a market dominated by U.S. productions. The research methodology used information contained in the archives of periodicals to articulate the context of the trailer in Brazil, focusing on the period in which imported trailers emerged and underwent mass-scale insertions in Brazil. Next, using the film material, case studies were prepared on the Brazilian trailers of the 1940s and the 1950s to identify rhetorical and aesthetic patterns in Brazilian advertisement production. This research hopes to contribute to a better understanding of the circulation (or the problems within the circulation) of Brazilian commercial productions of this period.